A new ring nematode, Xenocriconemella costaricense sp. nov., (Nematoda: Criconematidae) from Costa Rica - Peraza-Padilla, Walter (2024)
During nematode surveys of natural vegetation in forests of La Cima de Copey de Dota, San José, San José province, Costa Rica, a Xenocriconemella species closely resembling X. macrodora and related species was found. Integrative taxonomical approaches demonstrated that it is a new species described herein as X. costaricense sp. nov. The new species is parthenogenetic (only females have been detected) and characterised by a short body (276–404 μm); lip region with two annuli, not offset, not separated from body contour; first lip annulus partially covering the second lip annulus. Stylet thin, very long (113–133 μm) and flexible, occupying 30.5–47.8% of body length. Excretory pore located from one or two annuli anterior to one or two annuli posterior to level of stylet knobs, at 42 (37–45) μm from anterior end. Female genital tract monodelphic, prodelphic, outstretched, and occupying 35–45% of body length, with vagina slightly ventrally curved (14–18 μm long). Anus located 6–11 annuli from the tail terminus. Tail conoid and bluntly rounded terminus, the last 2–3 annuli oriented dorsally. Results of molecular characterisation and phylogenetic analyses of D2-D3 expansion segments of 28S rRNA, ITS, and partial 18S rRNA, as well as cytochrome oxidase c subunit 1 gene sequences further characterised the new species and clearly separated it from X. macrodora and other related species (X. iberica, X. paraiberica, and X. pradense).